Living Well in a World Worth Living in for All: Volume 2: Enacting Praxis for a Just and Sustainable Future - Reimer, Kristin Elaine; Kaukko, Mervi; Windsor, Sally; Kemmis, Stephen; Mahon, Kathleen (Springer Nature, 2024)
This open access book is the second of a two-volume series that explores how people are living well and creating a “World Worth Living in for All”. It engages in deep listening of voices from across the world and considers the role of education in creating a more just and sustainable world for the future. The book asks what can be learnt to create change in policy and practice in order to enact praxis. It showcases chapters from international authors who discuss current or new projects to address the overarching questions explored in the book. It also provides an overview of perspectives that connect both volumes and the individual projects presented together through the lens of practice architectures.